To calculate for the y-intercept, simply solve for an equation where x=0
9(0)-6y=-36
-6y=-36
divide both sides by -6
y=6
The y-intercept is 6
Answer:
Step-by-step explanation:
Good Morning If you can be more specific i can help you with this question but there is no table text me back if oyu still need help! ;)
A(x - x₁)(x - x₂) = 0
a=5, x₁=-3, x₂ = 3
so:
5(x-(-3))(x-3)=0
5(x+3)(x-3)=0
5(x²-9) = 0
5x² - 45 = 0 ← answer
The factor of three is six factor of two is to 3 is three factor of two is 22 is four and poster of four is 22 Answer